Pela conjugação das abordagens variacionista e difusionista (Revista de Estudos da Linguagem, 1992)
This study intends to show the cornplementarity of the variationist and the diffusionist models. The conjtillction of the two models makes it possible for tiS to controllinguistic,extralinguistic and lexical parameters, which leads to amore encompassing analysis since it allows us to take into account variable and invariable data. This is shown in our analysis of the variable process of Idf assimilation in the context/-ndol in words such as 'falando', 'mundo', 'ando'.